2016
DOI: 10.4103/2008-7802.183652
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment does not affect serum Vitamin D concentrations in patients with dyslipidemia: A randomized double-blind placebo-controlled cross-over trial

Abstract: Background:Hydroxymethylglutaryl-coenzyme A reductase inhibitors (statins) are antihyperlipidemic drugs with an established efficacy in stabilizing atherosclerotic plaques and preventing atherogenesis and reducing cardiovascular events. The purpose of this study was to determine the effect of simvastatin on serum Vitamin D status in dyslipidemic patients as Vitamin D status has an impact on monocyte/macrophage function and may also contribute to cardiovascular risk.Methods:Selected individuals (n = 102) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(25 reference statements)
2
8
0
Order By: Relevance
“…Perhaps, this could be the reason that most recent studies on this pleotropic effect of statins have failed to show any significant increase in vitamin D levels. 19 , 23 A recent meta-analysis of data from seven studies failed to show any significant effect of statins treatment on plasma concentrations of vitamin D. 9 All these reports lend support to our current results indicating lack of association between statin use and serum levels of vitamin D in type 2 DM patients. The multiple linear regression model to investigate this relationship while adjusting for other related factors mentioned above is a strength of this study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Perhaps, this could be the reason that most recent studies on this pleotropic effect of statins have failed to show any significant increase in vitamin D levels. 19 , 23 A recent meta-analysis of data from seven studies failed to show any significant effect of statins treatment on plasma concentrations of vitamin D. 9 All these reports lend support to our current results indicating lack of association between statin use and serum levels of vitamin D in type 2 DM patients. The multiple linear regression model to investigate this relationship while adjusting for other related factors mentioned above is a strength of this study.…”
Section: Discussionsupporting
confidence: 79%
“… 18 Similar results have been found by Mazidi et al on an Iranian population of patients with dyslipidemia. 19 On the contrary, Sathyapalan et al have reported increased concentration of 25(OH)D following therapy with atorvastatin in type 2 DM patients in UK. 20 Similarly, 4 studies (two carried out in Turkey, one in Spain and another one in Germany) have also shown increased serum levels of 25(OH)D following treatment with rosuvastatin and atorvastatin.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, 25(OH)D concentrations did not improve in the rosuvastatin group and, in fact, decreased a little over the 96-week study. Other studies have shown similar results 4954 . In the Atherosclerosis Prevention in Pediatric Lupus Erythematosus (APPLE) trial, a 3-year randomized, placebo controlled trial of atorvastatin in over 200 children and young adults with systemic lupus erythematosus (SLE), 25(OH)D concentrations did not change appreciably and were similar to the placebo group over the course of the study 54 .…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, Renjmark et al in a small randomized controlled trial among healthy postmenopausal women reported no significant differences in plasma 25(OH)D levels between subjects treated with simvastatin 40 mg/day for a year compared with their counterparts receiving placebo [15]. Likewise, Mazidi et al previously demonstrated in a randomized, double-blind, placebo-controlled trial lasting 30 days that simvastatin 40 mg/day did not have a significant effect on serum 25(OH)D levels [7]. Possible explanations for these contradictory results were attributed to unmeasured predictors of vitamin D status such as vitamin D intake and sun exposure [15].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, few observational studies and randomized controlled trials reported conflicting results regarding the effect of statins on 25(OH)D concentrations. Some studies described higher 25(OH)D concentrations among statin users, whereas others did not [7][8][9][10][11][12][13][14][15]. Nevertheless, these studies were limited by small sample size, subjects with acute coronary syndrome, individual generic statins, diabetics hospitalized, and postmenopausal women with osteopenia [7,9,11,[14][15].…”
Section: Introductionmentioning
confidence: 99%